Skyrybos pertvarka ir probleminiai jos klausimai - Drukteinis, Albinas (Lietuvių kalba, 2007)
This article is primarily devoted to those parts and cases of the rules passed by the Commission of the Lithuanian Language, where the users of those rules may face ambiguity, and the wider explanation of which may help the users to understand them better. Besides, the rules do not provide for all the cases, so their interpretation may be also useful for further revisions of the punctuation. The compliance of the theoretical provisions with the specific rules is also important.
Keywords: none